2018
DOI: 10.33076/2018.bdd.298
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinde Kronotipe Göre Besin Tüketiminin Değerlendirilmesi

Abstract: Amaç: Bu çalışma, üniversite öğrencilerinin kronotiplerinin belirlenmesi ve kronotiplerine göre besin tüketimlerinin karşılaştırılması amacıyla planlanmış ve yürütülmüştür. Bireyler ve Yöntem: Çalışmaya yaşları 19-31 yıl arasında olan, 198 erkek (%24.5) ve 609 kadın (%75.5) olmak üzere toplam 807 üniversite öğrencisi dahil edilmiştir. Bireylere genel özelliklerinin, beslenme ve uyku alışkanlıklarının sorgulandığı bir anket formu ve kronotipin belirlenmesi için “İnsan Sirkadiyen Ritminde Sabahçıl ve Akşam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
1
1
2
Order By: Relevance
“…According to the results of this study, there was a statistically significant increase in the MEQ scores as the BMI values increased. In other cross-sectional studies conducted with university students, it was observed that the BMI levels were higher in the morning types; these studies showed that there was a significant positive relationship between the BMI and MEQ scores, as seen in the current study [35,36]. Contrary to the results herein, in a study conducted among adolescents, evening chronotypes were found to have higher BMI values [37].…”
Section: Discussioncontrasting
confidence: 90%
“…According to the results of this study, there was a statistically significant increase in the MEQ scores as the BMI values increased. In other cross-sectional studies conducted with university students, it was observed that the BMI levels were higher in the morning types; these studies showed that there was a significant positive relationship between the BMI and MEQ scores, as seen in the current study [35,36]. Contrary to the results herein, in a study conducted among adolescents, evening chronotypes were found to have higher BMI values [37].…”
Section: Discussioncontrasting
confidence: 90%
“…25 Consistent with previous studies, morningness showed negative and EV showed positive associations with wake up times on weekdays and weekends. 26,27 Studies assessing eating habits and dietary intakes of the individuals according to chronotypes reported conflicting results. 5,[28][29][30] In a study of con-ducted with a sample of Iranian adults, it was indicated that energy intake, dietary intake and eating habits had no relationship with chronotype.…”
Section: Discussionmentioning
confidence: 99%
“…Yetişkinlerde yapılan bir çalışmada akşamcıl tiplerin kalsiyum, magnezyum, çinko, D vitamini, riboflavin ve B6 vitamini alımlarının daha düşük olduğu gösterilmiştir [11]. Üniversite öğrencilerinde kronotipin incelendiği bir çalışmada, sabahçıl bireylerin A vitamini ve folat alımının, akşamcıl ve ara tipteki bireylere göre daha yüksek olduğu saptanmıştır [12].…”
Section: Introductionunclassified
“…Buna ek olarak Çakır ve ark. 'nın üniversiteli öğrenciler üzerinde yapmış olduğu çalışmada sabahçıl bireylerin folat alımının daha fazla olması mevcut çalışma bulgularıyla benzerdir[12]. Ayrıca bu çalışmada SAA puanlarıyla BGÖ puanları arasında da pozitif bir ilişki bulunduğu saptandır.…”
unclassified